Are potential reductions in CO2 emissions via hybrid electric vehicles actualized in real traffic? The case of Japan. (January 2017) - Mishina, Yoshinori; Muromachi, Yasunori
Highlights: Potential CO2 reductions via hybrid electric vehicles (HEVs) are offset markedly. Gap between the on-road and test fuel economy of HEVs is considerably large. Direct rebound effects of HEV use are in the range of other passenger vehicles. Equity policies would be required for urban and rural regions. Abstract: The number of private passenger hybrid electric vehicles (HEVs) in use in Japan has increased rapidly since 2009. One of the advantages of HEVs over conventional passenger vehicles lies in the higher fuel economy obtained by recent technological innovations, which helps reduce carbon dioxide (CO2 ) emissions from transport. However, are the potential reductions in CO2 emissions via HEVs actualized in real traffic in Japan? To answer this question, this study estimates the regional gap between on-road fuel economy and fuel economy in the regulated test procedures (test fuel economy) of HEVs and regional direct rebound effects of HEV use during 2010–2013. To estimate the direct rebound effects, a methodological framework of the Modified Laspeyres Index (MLI) decomposition is proposed to quantify the contribution of kilometers traveled per vehicle to aggregate the differences between CO2 emissions per HEV and those per standard/small vehicle. The results show that the potential reductions in CO2 emissions offered by the higher test fuel economy of HEVs have been offset markedly by the deterioration in test fuel economy and the direct rebound effects in real traffic over the period. An increase in fuel prices by implementing a fuel tax increase would be one method to improve the on-road fuel economy of HEVs and reduce the direct rebound effects. However, equity policies would be required for urban and rural regions. The findings present helpful information to policymakers wishing to promote higher fuel economy vehicles to reduce CO2 emissions from transportation.